Chicken or checkin'? Rational learning in repeated chess games - Christer Gerdes; Patrik Gränsmark; Michael Rosholm (Institute for the Study of Labor (IZA), 2011)
We examine rational learning among expert chess players and how they update their beliefs in repeated games with the same opponent. We present a model that explains how equilibrium play is affected when players change their choice of strategy when receiving additional information from each encounter. We employ a large international panel dataset with controls for risk preferences and playing skills whereby the latter accounts for ability. Although expert chess players are intelligent, productive and equipped with adequate data and specialized computer programs, we find large learning effects. Moreover, as predicted by the model, risk-averse players learn substantially faster.
urn:nbn:de:101:1-201107283903
Keywords: C73; D83; 330; rational learning; risk aversion; beliefs